KONSEP WEWANGIAN BAGI WANITA: STUDI PERBANDINGAN SYARAH HADIS IMAM ABDURRAHMAN AL-MUBARAKFURI DAN SYEIKH AL-'AZIZI - Triadi Ulmawan; Hidayati Hidayati; Melia Novera (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Ar-Rahman, 2025)
The use of fragrance has become an integral part of daily life for many Muslims, to the extent that it is now considered a personal necessity. Definitions of fragrance may vary among individuals; for instance, Imam An-Nawawi defines it as any substance used to enhance personal scent. In Islam, the application of fragrance is considered a Sunnah, as it was regularly practiced and encouraged by the Prophet Muhammad (peace be upon him). However, Islamic teachings distinguish between men and women regarding the use of fragrance, with more restrictions placed on women to prevent undesirable social consequences. This study employs a library-based (literature) research method and utilizes a qualitative approach to explore the issue in greater depth. The research compares the perspectives of Imam Abdurrahman Al-Mubarakfuri and Sheikh Al-‘Azizi concerning the permissibility and limitations of fragrance use among women. The findings suggest that women are prohibited from wearing strong or noticeable fragrances in public spaces where they may encounter non-mahram men, as this act is likened to sinful behavior, including that of a fornicator, according to certain interpretations. Nevertheless, women are permitted to use fragrance under specific conditions that align with the guidance provided by the Prophet Muhammad (peace be upon him).